2020
DOI: 10.1177/0192513x20925508
|View full text |Cite
|
Sign up to set email alerts
|

“It Takes a Lot of Planning”: Sexual Minority Young Adult Perceptions of Gay and Lesbian Parenthood

Abstract: Lesbian and gay parents are becoming more prevalent, visible, and accepted in the United States. Despite these shifts, legal and social obstacles continue to shape pathways to parenthood. For many lesbians and gay men, access to parenthood is difficult, uncertain, and varies geographically. Using focus group interviews, this study explores how 36 Midwestern gay, lesbian, and bisexual young adults without children perceive gay and lesbian parenting and their own parenthood prospects. Themes included perceptions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 52 publications
(61 reference statements)
0
12
0
Order By: Relevance
“…Despite systemic advancements in the visibility and perceived legitimacy of LGBT parenting, sociohistorical contexts are complex (Park et al, 2020;Perrin et al, 2019). Many gay, bisexual, and other sexual minority men are still informed, through social media messages and negative cultural attitudes, that they cannot be fathers (Folgerø, 2008;Shenkman et al, 2020).…”
Section: Sociohistorical Contextsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite systemic advancements in the visibility and perceived legitimacy of LGBT parenting, sociohistorical contexts are complex (Park et al, 2020;Perrin et al, 2019). Many gay, bisexual, and other sexual minority men are still informed, through social media messages and negative cultural attitudes, that they cannot be fathers (Folgerø, 2008;Shenkman et al, 2020).…”
Section: Sociohistorical Contextsmentioning
confidence: 99%
“…The development of assisted reproductive technologies (ART) and the growing visibility of same-sex parent families have broadened family scholarship to include LGBT (lesbian, gay, bisexual, transgender) families and parenthood (Park et al, 2020). Empirical research has shifted over the past few decades to include the exploration of "planned gay parenthood," the purposeful way in which gay men, often in the context of a same-sex relationship, demonstrate an interest in fatherhood.…”
Section: Introductionmentioning
confidence: 99%
“…[9,21] As the procreative identity framework suggests,[8] socioeconomic, legal, and cultural barriers can intensify sexual minority individuals' hesitance or reluctance to seek parenthood. [14,15,22] Several studies have investigated how changes in the legal recognition of SSM may in uence sexual minority individuals' desire, intention towards, or actual, childbearing. For example, Italy recognized same-sex civil unions in June 2016, yet access to parenthood through donor insemination or surrogacy or adoption is still not allowed.…”
Section: Childbearing Desire Among Sexual Minority Menmentioning
confidence: 99%
“…[25,26] The current study Although previous studies have suggested that judicial rulings and marriage equality policy can be associated with sexual minority men's childbearing aspirations, their results are either qualitative or crosssectional. [8,14,15,22,27] To date, no longitudinal research has been conducted to pinpoint the change in sexual minority men's childbearing desire as a function of the legalization of SSM. A unique opportunity to collect prospective data emerged in Taiwan when the Judicial Yuan made the ruling, Interpretation No.…”
Section: Childbearing Desire Among Sexual Minority Menmentioning
confidence: 99%
See 1 more Smart Citation